FUTURE SERENITY: EMBRACING ZAKAT IN THE FURNITURE INDUSTRY - Suhartono, Suhartono; Anwar, Aan Zainul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
The furniture industry is at a turning point in its history, where ethical business practices and social responsibility are becoming more and more important. Furniture producers and merchants can fit with consumer values and improve their social effect by adopting zakat, the Islamic concept of charitable giving. The incorporation of zakat into the furniture industry is examined in this essay, with an emphasis on how it could lessen social inequities and promote communal growth. The lives of impoverished families in Jepara can be improved and poverty can be reduced by creating zakat funds and increasing awareness. This study emphasises zakat's function as a catalyst for social justice and economic equity using Islamic qualitative research methods. With its defined routes for zakat donations that guarantee businesses obtain the right tax deductions, the Integrated Zakat Advantage (IZA) framework promotes cooperation between BAZNAS, Mustahiq communities, the Directorate General of Taxation, and business owners. Through this collaboration, BAZNAS is able to provide zakat to local communities in an efficient manner, creating a mutually beneficial relationship that benefits both enterprises and the communities they serve. Businesses can position themselves as leaders in corporate social responsibility and improve customer loyalty and brand reputation by fostering a culture of giving through zakat. This will ultimately help create a society that is more compassionate and just.